Passenger car units of vehicles on Singapore expressways - Tan, Ying Kiat. (2010)
Passenger Car Units (PCU) for vehicles on expressways in Singapore was developed for level of service LOS D and LOS E when the posted speed limit was 80 km/h. The posted speed limits for most expressway segments in Singapore have now been raised to 90 km/h, and the vehicle speed limits for goods vehicles have also been raised. In order to determine whether the current PCU values are still valid, data would be extracted from recorded tapes and multiple linear regression method would be selected to establish PCU values.